Effects of the health belief model following acute exacerbation of chronic obstructive pulmonary disease in a hospital in China - Ji, Mei; Wang, Ai-Hong; Ye, Jun; Shen, Ya-Hui; Chen, Chun-Mei; Yu, Chen; Li, Li-Fang (Journal of Thoracic Disease, 2019)
Background: This study aims to investigate the effects of education with health belief model (HBM) on anxiety and fatigue among patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods: Patients with AECOPD admitted into Taizhou People’s Hospital, Jiangsu, China between December 2012 and October 2013 were randomly selected for the present study according to random number table. A total of 99 cases with anxiety were included. These patients were divided into two groups: experimental group educated by HBM (n=47), and control group educated by conventional method (n=52). The scores for anxiety and fatigue were evaluated using the self-rating anxiety scale (SAS) and multidimensional fatigue inventory (MFI-20). Results: After educational intervention by HBM, patients achieved a significant decrease in anxiety and fatigue scores, when compared to patients in the control group, who were educated by the conventional method at the time of admission, discharge, and 6 weeks after discharge (P